Sequence analysis of a PM2-DNA anti-Z-IgG-binding region. Issue 10 (October 1984) - Miller, F. D.; Winkfein, R. J.; Rattner, J. B.; Van de Sande, J. H.
Abstract : An anti-Z-antibody-binding region between PM2-DNA map units 0.05 and 0.18, containing approx. 25% of the bound PM2 antibody molecules (1, 2) has been sequenced. Analysis of this PM2 DNA sequence from map units 0.00 to 0.175 demonstrates that alternating purine/pyrimidine tracts capable of adopting the left-handed conformation are present within this antibody-binding region. Longer (GC)n-rich tracts are clustered together and comprise seven alternating purine/pyrimidine-rich areas (48%–84%) ranging from 19 to 142 nucleotides in length. The DNA located between these alternating purine/pyrimidine-rich areas exhibit a low level (0%–19%) of this sequence arrangement. There is a very strong correlation between the alternating purine/pyrimidine-rich areas and the anti-Z-DNA-IgG-binding sites. Nucleotides 1461–1583 of the PM2-DNA genome encode the bacteriophage capsid protein IV. One of the PM2 left-handed sites is located within this protein-coding sequence; a B-to-Z transition within this site may be involved in protein-IV gene regulation in vivo.